Age-related and sex-related changes in the normal soft tissue profile of native Northern Sudanese subjects: a cross-sectional study. Issue 2 (February 2016) - Sforza, Chiarella; Dolci, Claudia; Gibelli, Daniele M.; Codari, Marina; Pucciarelli, Valentina; Ferrario, Virgilio F.; Elamin, Fadil
Abstract: Information about age-related and sex-related normative measurements of the nasolabial region in native Northern Sudanese subjects is scanty. We have therefore used a hand-held laser scanner to measure nasolabial angles and distances, and collected the 3-dimensional coordinates of seven landmarks on the facial soft tissues from 654 healthy native Northern Sudanese subjects (327 male and 327 female, aged 4-30 years). From these we calculated five angles and two linear distances and took the mean (SD) for age and sex, and compared them using factorial analysis of variance. All measurements analysed were significantly modified by age in both sexes (p< 0.01 ) except for the distance from the lower lip to Ricketts' E-line. Sex had a significant effect on the mentolabial and maxillary prominence angles and both distances (p < 0.005 ). Nasal convexity and the interlabial angle became more obtuse with growth, while the nasolabial and mentolabial angles reduced progressively with female subjects having significantly more obtuse mentolabial angles(p < 0.001 ). The maxillary prominence angle progressively decreased during childhood, and increased after adolescence, with larger values in male subjects. The upper and lower lip distances from Ricketts' E-line were also significantly larger in male subjects(p < 0.003 ), but the difference reduced with age. Overall, there were several differences when we compared our data with published data for African and white subjects, which points to the need for ethnic-specific data. Measurements collected in the current study could be used for the quantitative description of facial morphology in native Northern Sudanese children, adolescents, and young adults.